Psycholinguistic Studies: Acquisition of Indonesian Phonology in Down Syndrome Children - Sinaga, Lara Desma; Gustianingsih; Zein, T. Thyrhaya (Universitas Pendidikan Ganesha, 2023)
Language acquisition is a process that takes place in a child's brain when he acquires his first language or mother tongue which means language acquisition in relation to his first language. This study aims to analyze the acquisition of Indonesian phonology in Down syndrome children. This study was conducted on 5 Down syndrome, age range of 6-9 years. This study use Blumstein's theory of speech changes is used to determine the change of speech sounds and Jacobson's theory is used to determine the acquisition of phonology Indonesian and Jean Piaget's theory is used to describe the language development of them. The method used is proficient and record. It was found that the five respondents in pronouncing several words there was a change in the sound of speech, namely sound Deletion (Omision), sound addition (Addition), and sound replacement (Substitution). They have also acquired some of the Indonesian vowel sounds [i], [ u], [e], [o] and [a]. They can produce several vowels sounds either at the beginning, middle or end words. There are some consonants that have been acquired Indonesian and there are some consonant sounds that have not been obtained, [w], [f]. [z], and [h]. The phonological development is the stage of holoprastic. Their chronological age is 6 to 9 years, but the age of language acquisition is equivalent to the age of two years.